ЎЗБЕК АНЪАНАВИЙ КАШТАДЎЗЛИГИНИНГ СПЕКТРАЛ - ВАРИАТИВЛИГИ - Шомирзаев, М.Х. (SCIENCE and SOCIETY, 2019)
The article describes the spectral variability of Uzbek traditional embroidery, based on the integration of physics, mathematics, chemistry, technology, etc.
Keywords: embroidery; crafts; jewelry; chorsi; sheets; skullcaps; businessmen; microfirms; events; traditional; exhibition